Evaluating the Efficacy and Safety of Poly-d,l-lactic Acid Administered via Cannula Technique in the Treatment of Moderate Rosacea - Wan, Jovian; Seo, Suk Bae; Yi, Kyu-Ho (Plastic and reconstructive surgery. Global open, 2025)
Rosacea is a chronic skin condition typically managed with treatments targeting surface symptoms such as erythema. Long-term solutions may require addressing deeper skin alterations. This study explored the efficacy and safety of poly-d,l-lactic acid (PDLLA, Juvelook, VAIM Inc., Seoul, Korea) administered via a cannula technique for moderate rosacea treatment. Four participants (32-62 years of age) with moderate rosacea unresponsive to conventional therapies underwent 3 PDLLA treatments at 3-week intervals. A 25G blunt-tip cannula was used to administer PDLLA into the subdermal layer. Erythema was assessed at baseline, 4 weeks, and 12 weeks using the Clinician's Erythema Assessment scale. Patient satisfaction was measured on a 4-point scale. PDLLA showed significant efficacy in reducing erythema and improving skin structure. All participants reported improved Clinician's Erythema Assessment scores with sustained effects at the 12-week follow-up. Patient satisfaction was high, and adverse effects were minimal (mild edema resolving spontaneously). PDLLA via cannula shows promise for treating refractory rosacea by addressing both superficial and deeper skin factors. Further research is needed to validate long-term efficacy and explore mechanisms of action.